2012
DOI: 10.1007/s00586-012-2228-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a bone substitute (CERAMENT™) as an alternative to PMMA in percutaneous vertebroplasty: 1-year follow-up on clinical outcome

Abstract: Data show that CERAMENT can be a substitute of PMMA in the treatment of osteoporotic and traumatic vertebral fractures, especially in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…The composite of HA and calcium sulfate has been used clinically with good results in various indications [58][59][60][61][62][63][64][65][66][67], which is further explained below.…”
Section: Clinical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The composite of HA and calcium sulfate has been used clinically with good results in various indications [58][59][60][61][62][63][64][65][66][67], which is further explained below.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Marcia et al reported no new fractures studying vertebroplasty treatment with HA/calcium sulfate in 33 patients during 1 year [62]. Siemund et al concluded that the biphasic material was safe and effective in the treatment of acute osteoporotic vertebral body fractures and Marcia et al stressed the advantage to use this material in young patients due to its bone healing ability [62,64].…”
Section: Vertebroplastymentioning
confidence: 98%
See 1 more Smart Citation
“…[45][46][47][48][49] Recent studies showed that few new-generation bioactive bone cements have been found to induce new bone formation and also have good mechanical stability. 50,51 Bioactive composite materials prepared from acrylic cement in conjunction with ceramics showed good radioopacity. 52 Cortoss, a composed material-based bone cement currently undergoing clinical trials for PVP and BKP is composed of terpolymer resin with combeite glass-ceramics.…”
Section: Anatomy and Physiopathologymentioning
confidence: 99%
“…Its higher radiopacity enabled visualization of the 6 cement whilst injecting (figure 11) [21]. However, iohexol generates artefacts in the microCT images that 7 prevent a correct evaluation of the cement inside the bone defect, impairing the evaluation of injected 8 cement volume and the determination of possible leakage (figure 12).…”
Section: Resultsmentioning
confidence: 98%